Розвиток організаційного механізму комерціалізації об'єктів інтелектуальної власності на основі функціонального підходу - Перерва, Петро Григорович; Косенко, Андрій Васильович (Харківський національний економічний університет ім. Семена Кузнеця, 2009)
The mechanism of commercialization of intellectual innovations, which include an economic constituent (the determination of intellectual property objects' cost), and also organizational constituent – forming of the organizational forms of commercialization with the use of process and functional approaches – are worked out.
Keywords: процес виробничий; підприємство машинобудівне; брокерство інноваційне; ефект збуту; трансфер технологій